Analisis Pendapatan Usaha Peternakan Ayam Buras Petelur dengan Menerapkan Teknologi Pakan Limbah Ternak Sapi (Studi Kasus di Kelompok Tani Ternak Sato Nadi, Kecamatan Tembuku, Kabupaten Bangli) - SRIYANTO, SRIYANTO; PUTRA, I GEDE SETIAWAN ADI; DHARMA, I PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.1, Januari 2017DO - 10.24843/JAA.2017.v06.i01.p10, 2017)
Analysis of Operating Revenues ofLaying Domestic Poultry by Applying the Waste Cattle Feed Technology (A Case Study in Farmers Group of Sato Nadi,Sub-District of Tembuku, Bangli Regency) Feed is the major determinant in the success of farming and as a means of support forthe improvement of productivity of poultry. During this time the availability oflivestock feed has been supplied from outside the island of Bali and is relativelyexpensive. This is an opportunity for farmers in the village of Jehem to be able tomeet their needs for cheaper poultry feed mainly for the domestic poultry madefromcattle waste. The purpose of this study was to determine the level of incomereceived by farmers and the constraints faced in domestic poultry farm. This researchwas conducted in the farmer groups of Sato Nadi, Sub-District of Tembuku, BangliRegency.The total sample was as many as 22 farmers involved in the business oflaying domestic poultry. The analytical method used was the method of quantitativeand qualitative descriptiveanalysis, analysis of farming, and the R / C ratio. Theresults showed that the income received by farmers in the domestic poultry farmergroup of Sato Nadi, Jehem Village, Sub-District of Tembuku, Bangli Regency wasRp 1,901,847.80 / 100 chickens in the group of conventional feed, and Rp 2,640,111, 78/100 chickensfor the group that applied Cattle waste feed, and R / C Ratioobtained respectively of 1.11 and 1.15. The twofarmer groupsof domestic poultryfarm are feasible to be developed and profitable. The constraint faced by the farmerswas factor of the increase in feed prices that are not accompanied by the rising ofproduction prices cause smaller profits for the farmers. Suggestions that can be givenin this research are the governmentshould reduce variable costs through the use offeed of cattle manure flour and good profits can be obtained if the farmers willing toproduce the feed by their own and do not buy the finished feed.
Keywords: poultry, cattle, farms